Enredaderas ornamentales nativas de Misiones - Gartland, H.m.; Bohren, A.v. (Posadas, Misiones Universitaria, 1996)
Flora Argentina
Donacion D. Miranda
Keywords: Flora; Etnobotanica; Argentina; Nea; Ornamentales; Trepadoras; Enredaderas